Foeniculum vulgare (Fennel) promotes functional recovery and ameliorates oxidative stress following a lesion to the sciatic nerve in mouse model. Issue 9 (21st July 2019) - Imran, Ali; Xiao, Lei; Ahmad, Waseem; Anwar, Haseeb; Rasul, Azhar; Imran, Muhammad; Aziz, Nimra; Razzaq, Aroona; Arshad, Muhammad Umair; Shabbir, Asghar; Gonzalez de Aguilar, Jose‐Luis; Sun, Tao; et al.
Abstract: Peripheral nerve injury is one of the major health concerns of the present era which can lead to the long‐lasting disability and even demise. Currently, no effective and side effect free remedy exists and exploration of effective therapeutic strategies to regain functional outcome is a need of hour. In the present study, we used BALB/c mice ( N  = 14 age, 10–12 weeks & weight 32–34 g) that were divided into two groups: Normal chow ( n  = 7) and Fennel chow ( n  = 7) group. Here, we have explored the role of crude Foeniculum vulgare mill seeds in promoting functional recovery following a mechanical insult to the sciatic nerve by an oral administration of a crude dose of 500 mg/kg BW. The recovery of both sensory and motor functions was significantly ( p  > .05) accelerated in the treatment group, assessed by behavioral analyses alongside total antioxidant capacity increase. Conclusively, F. vulgare can be a potential therapeutic candidate for accelerating functional recovery after peripheral nerve injury. Practical applications: The outcomes of study have vital practical application both for scientists and consumers. The therapeutic role of phytochemicals on functional recovery has not been explored yet. This study will help figure out plant based regimen as booster for brain health and intervention against traumatic nerve injuries. Moreover, it may also attract the food and pharmaceutical industries to formulate cost effective therapeutic products. Likewise, it can prove instrumental for scientists for advance research on this aspect with more mechanistic targets.